Diagnóstico da colheita e beneficiamento de sementes de algodão na região sul de Goiás - Ferreira, Ivan Cardoso [UNESP] (2009)
This study aimed to characterize the phenological cotton, obtaining the maximum potential yield (RPM), the quantification of losses in the harvesting of cotton in stone and analysis of the quality of cotton seed saved after two methods of treatment in the municipality of Ipameri -GO. For this reason the experiment was conducted on three properties (farms) the cotton, using the completely randomized design with 10 replications. The characterization of the farming was done using analysis of phenological data was obtained which enabled the number and average weight of seed ha-1 ha-1 and featherweight (RPM). This material went through tests that assessed their quality after the treatment, in addition to the quantification of losses that took place during the harvest, allowing a diagnosis of the harvest of cotton in the South of Goiás The values for the RPM of plume ranged from 1461 kg ha -1 and 1646.34 kg ha-1 per hectare. The values of RPM seed ranged from 1694.72 kg ha-1 and 1922.9 kg ha-1 per hectare. The total losses found in this study stood at around 5.1%, 3.5% and 7.5% respectively for the three properties, remaining within the limits considered acceptable. In none of the tests of germination or force were significant differences in quality of seed recipients manually or mechanically.